Pengaruh Kualitas Pelayanan Air Bersih dan Sistem Informasi Biaya Tagihan Air Terhadap Kepuasan Pelanggan PDAM Tirta Silaupiasa Kisaran - Vebryanty, Evita; Yuliana, Yayuk (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
This study uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables. The sampling technique in this study used the Random Sampling Technique, namely to determine a random sample of 100 respondents who were customers of PDAM Tirta Silaupiasa Kisaran. The analysis technique used is multiple linear regression analysis. The suitability test using the t test and F test was carried out to test the effect partially and simultaneously between the independent variables and the dependent variable with the assumption that other variables are considered constant. Based on the results of multiple linear regression tests, it is known that the multiple linear regression equation in this study is: Y = 3.940 + 0.109 (X1) + 0.225 (X2). The positive equation value indicates that if there is an increase in Service Quality and Cost Information System, then Customer Satisfaction will also increase. Based on the results of the F test, the calculated f value is 60,091 with a sig level of 0.000, therefore the sig value is 0.000 > 0.05 with a calculated f value of 60,091 > f table 3.94. This indicates that Ho is rejected, so it can be concluded that the independent variables X1 and X2 simultaneously have a positive and significant effect on the dependent variable Y. Based on the test results, the coefficient of determination R2 is 0.533, thus indicating service quality and cost information systems simultaneously jointly influence the satisfaction of partnered customers in PDAM Tirta Silaupiasa Range of 53.3% with the remaining 46.7% which is influenced by factors - factors outside the research.